Upper body contributions to power generation during rapid, overhand throwing in humans - Roach, N. T.; Lieberman, D. E. (The Journal of Experimental Biology, 2014)
High-speed and accurate throwing is a distinctive human behavior. Achieving fast projectile speeds during throwing requires a combination of elastic energy storage at the shoulder, as well as the transfer of kinetic energy from proximal body segments to distal segments. However, the biomechanical bases of these mechanisms are not completely understood. We used inverse dynamics analyses of kinematic data from 20 baseball players fitted with four different braces that inhibit specific motions to test a model of power generation at key joints during the throwing motion. We found that most of the work produced during throwing is generated at the hips, and much of this work (combined with smaller contributions from the pectoralis major) is used to load elastic elements in the shoulder and power the rapid acceleration of the projectile. Despite rapid angular velocities at the elbow and wrist, the restrictions confirm that much of the power generated to produce these distal movements comes from larger proximal segments, such as the shoulder and torso. Wrist hyperextension enhances performance only modestly. Together, our data also suggest that heavy reliance on elastic energy storage may help explain some common throwing injuries and can provide further insight into the evolution of the upper body and when our ancestors first developed the ability to produce high-speed throws.